Tinjauan Yuridis terhadap Akta Hibah kepada Ahli Waris tanpa Persetujuan Ahli Waris Lainnya - Zul Kifli ZA; Sakka Pati; Aulia Rifai (LPPM Universitas Ekasakti Padang, 2023)
This study discusses the juridical review of the deed of grants to heirs without the approval of other heirs. This type of research is a type of library research, in other words, collecting library data, discussing doctrines or principles in the science of law and various other sources that examine or examine the issue of applying positive legal principles or norms. In the perspective of legal research, resolving a legal issue through legal research requires certain approaches as a basis for compiling appropriate, logical and accurate legal arguments. The research approach used in this thesis are: 1) statutory approach and 2) conceptual approach. Normative legal research is library research, namely research on secondary data. The sources of legal materials used in this research are primary, secondary and tertiary legal materials. The results of this study are: 1) A grant deed made authentically to heirs without the approval of other heirs is still considered valid if there has not been a court decision to cancel the grant deed. In the case of grant disputes, the Religious Courts have the authority to simultaneously decide on property or other civil disputes related to the object of the grant dispute if the subject of the dispute is Muslim people. In Islam, grants to heirs can be counted as inheritance, if the grant exceeds the inheritance, the excess grant should be included in the inheritance boedel and 2) PPAT is responsible civilly for the deed of grants to heirs without the knowledge of other heirs for losses received by experts other heirs if related to intention, negligence and/or negligence in making the deed of grant deviating from the formal and material requirements. PPAT can not only be subject to administrative sanctions but also be sued for civil compensation by the aggrieved parties.